2017
DOI: 10.1177/2156587216687696
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Hydroalcoholic Extract of Zingiber officinale Roscoe (Ginger) on Ethanol-Induced Reproductive Toxicity in Male Rats

Abstract: This study was conducted to evaluate the prophylactic effect of ginger extract on ethanol-induced reproductive toxicity in male rats. Twenty-eight adult male Sprague-Dawley rats were randomly divided into 4 groups and treated daily for 28 days as follows: control, control-ginger (1 g/kg of body weight [BW]/day by gavage), ethanol group (ethanol 4 g/kg of BW/day by gavage), and ginger-ethanol group. At the end of the experiment, all the rats were sacrificed and their testes were removed and used for measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 66 publications
(96 reference statements)
9
35
2
Order By: Relevance
“…Many studies believed that taking zinc supplements and ginger could improve metabolic disorders such as obesity, DM, and MS by several mechanisms (Li, Tran, et al., 2012; Miao et al., 2013; Ruz et al., 2019; Wang et al., 2017, 2019). Ginger improves metabolic disorders by increasing the thermogenesis, the energy expenditure, the lipolysis, and by inhibiting the lipogenesis and the lipid accumulation and the intestinal absorption of dietary fat (Akbari et al., 2017, 2019; Ebrahimzadeh Attari et al., 2018; Li, Tran, et al., 2012; Maharlouei et al., 2019; Wang et al., 2017; Zhu et al., 2018). In addition, it was reported that ginger prevents obesity through the regulation of energy metabolism and activation of browning in HFD‐induced obese mice (Wang et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies believed that taking zinc supplements and ginger could improve metabolic disorders such as obesity, DM, and MS by several mechanisms (Li, Tran, et al., 2012; Miao et al., 2013; Ruz et al., 2019; Wang et al., 2017, 2019). Ginger improves metabolic disorders by increasing the thermogenesis, the energy expenditure, the lipolysis, and by inhibiting the lipogenesis and the lipid accumulation and the intestinal absorption of dietary fat (Akbari et al., 2017, 2019; Ebrahimzadeh Attari et al., 2018; Li, Tran, et al., 2012; Maharlouei et al., 2019; Wang et al., 2017; Zhu et al., 2018). In addition, it was reported that ginger prevents obesity through the regulation of energy metabolism and activation of browning in HFD‐induced obese mice (Wang et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that ginger prevents obesity through the regulation of energy metabolism and activation of browning in HFD‐induced obese mice (Wang et al., 2019). Moreover, it plays a key role in controlling appetite (Mansour et al., 2012) and homeostasis of some essential elements such as zinc (Akbari et al., 2017). Okamoto et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that natural antioxidants have great potential for protecting DNA and other biomolecules from damages caused by oxidation [10,11]. Ginger (Zingiber officinale) with a wide range of biological properties contains high amount of antioxidants, such as gingerol and shogaol [12,13]. Ginger has been shown to lower lipid peroxidation by maintaining antioxidant enzymes activities and increasing glutathione level in the rat blood [14].…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant assay of C . colocynthis was carried out according to the DPPH (2,2‐diphenyl‐1‐picryl‐hydrazyl‐hydrate) methods described earlier (Akbari, Nasiri, Heydari, Mosavat, & Iraji, ). DPPH is a stable free radical with purple color, which demonstrates a strong absorption at 517 nm.…”
Section: Methodsmentioning
confidence: 99%